Application of Scientific Literacy in Research Class Activities - Tina Rahmawati (Postgraduate, University of Mataram, 2023)
This study aims to describe the application of scientific literacy in research class activities at SMA IT Abu Bakar Boarding School Kulon Progo. This research is a descriptive study with a qualitative approach. The subjects of this study were school principals, vice principals in curriculum, literacy program managers and research methodology teachers. Methods of data collection by interview and documentation. The results of the study are as follows: (1) The implementation of the research class activities includes providing material, writing proposals and research results, presenting research results, printing research results, and assessing. The guidelines used today still use modules from research smes. (2) The implementation of scientific literacy is carried out by making reading movements before or when learning is carried out, campaigning for literacy culture, and selecting reading materials for students.